3D printable biomaterials for orthopedic implants: Solution for sustainable and circular economy. (October 2020) - Yadav, Dinesh; Garg, Ramesh Kumar; Ahlawat, Akash; Chhabra, Deepak
Abstract: In the last few years, 3d printable biomaterials has been tremendously utilized in the fabrication of orthopaedic implants because of its light weight, minimum material wastage, porous structure for tissue growth, ease of making patient specific and any complex topology implants. The sustainability of 3D printing technique along with using sustainable biomaterials made the development of implants more accurate, compatible with human body along with 3 R's i.e. reduce, reuse and recyclable. This R-framework includes three methods of rising circular economy which make orthopedics healthcare more capable beyond the limits of traditional strategies and results on demand patient specific implant production with increased durability Operation Management apart from 3R concept also use ReSOLVE framework i.e. Regenerate, Share, Optimize, Loop, Virtualize and Exchange to organize circularity principles in business model. In this work, 3D printable and traditional materials are classified on the basis of sustainability and circularity concept. The permanent metallic biomaterials and the resorbables biomaterials have been comprehensively reviewed with the emphasis on reutilization, biocompatibility and mechanical properties. The 95% of the orthopaedic implants still using metallic biomaterials because of their high ultimate tensile strength (UTS), fatigue strength, durability and toughness. Advance surface treatments are needed to make metallic materials implants biocompatible. It is observed that bioresorbable implants are the solution for sustainability as compare to permanent biomaterials. The main concern of the bioresorbable implants is the low UTS, which limits its usage only for soft bones and not for long bones where higher UTS is a necessity. The 3D printed implants have low fatigue strength because of imperfections. For longer bones, more 3D printable bioresorbable materials need to be developed with higher UTS, toughness and fatigue strength so as to broaden their application base. These 3D printable bioresorbable materials will make orthopaedic industry more sustainable and oriented towards circular economy. Highlights: Biocompatibility of orthopaedic implant biomaterials has been investigated. Circularity concept and sustainability of biomaterials implants has been conferred. Biomaterials are classified based on 3D printable and traditional biomaterials as well as nature of materials/their sources. The significant mechanical properties of implants along with human body bones have been discussed. The important properties of biomaterials to be 3D printable have been reviewed and advance surface treatments of metallic biomaterials to make them biocompatible have also been conversed.